TAXONOMIC STUDY OF EPIDERMIS AND INDUMENTUM FOR SPECIES OF VERONICA L.(PLANTIGNACEAE) IN NORTHERN IRAQ - Al-Abide, Naglaa Mustafa; Al-Abide, Naglaa Mustafa (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims to study the characteristics of the Epidermis, the midrib area and stem of six species of wild land in northern Iraq belonging to the Plantignaceae family and species: Veronica anagills-aquatica L., Veronica anagilloides, Veronica arvensis L., and Veronica cymbalaria bod. , Veronica persica L. and Veronica Polita Fries. For the rest of the species studied in the world, its studied qualities have been compared with its peers. The results showed that the qualities of the epidermis indumentum, Crystals and venation leaves are of taxonomic importance as all species were special because of the presence of glandular and eglandular hair of the species .In the upper epidermis of Veronica polita.